Indonesian national qualifications framework competence on the doctoral studies in economics at the Universitas Trisakti - Soeharjoto, Soeharjoto; Ratnawati, Nirdukita; Tribudhi, Debbie Aryani (Trigin Publisher, 2024)
Globalization brings major changes to the order of life in the world, especially in the fields of education and labour. This has made it easier for people to migrate to get jobs. Indonesian Government is working to improve the quality and quantity of human resources through education, by implementing the Indonesian National Qualifications Framework programme. The college that runs this program, has produced an external alumni, so it can be used as an indicator of the success of the curriculum. To do that, we need to do a tracer study to find out what competence he has. The study, conducted using a descriptive statistical method, using samples of 43 respondents, whose sampling using purposive samplings, from the Alumni of Universitas Trisakti Doctoral Study in Economics in 2021/2022. Research data used Likert scale, the analysis is carried out by calculating the ratio of types of the type of competencies, based on the provisions of the Indonesian National Qualifications Framework program, which includes attitudes, general skills, special knowledge skills. As for the results, the kind of competence that its alumni possess with competence is very high at 54.75 percent and high at 45.25 percent. This learning achievement, has been in line with its objective, because all of the access to learning knowledge, general skills, special skills and attitudes are above average. Very high attitude achievements of 65.35 percent and high as 34.65 percent, very high general skills of 60 percent and higher as 40 percent, special knowledge very high of 47.09 percent and height of 52.91 percent, highest knowledge of 40.47 percent and tallest of 59.53 percent. Higher education institutions need to improve their alumni’s soft skills of and the achievement of the Indonesian National Qualifications Framework to be very high, by collaborating with alumni and industry, to develop the curriculum to fit the needs of the labor market.